T?cnicas de aloca??o adaptativa do comprimento dos filtros digitais de equalizadores para sistemas de HDTV no padr?o ATSC - Lopes, Estevan Marcelo (2002)
The purpose of the present thesis is to optimize the performance of the equalization system in ATSC (8 VSB modulation) digital television receivers, making them more efficient and with a lower processing load. The main idea is to change the lengths of the FIR digital filters through an automatic and adaptive process, so that they can act only on sockets that are important for the channel equalization process. The actualization of the gain gains is performed using the blind equalization technique called GPEA-Godard. We have developed an adaptive LE and DFE equalizer, which can be used to implement a receiver in the ATSC standard. We also developed an equalizer to be used in sparsely dispersed channels. We show, through simulations, that the channel can be better equalized if the length of the digital filters changes. Standards for digital television; Equalization systems for digital television; EQ: limited bandwidth channel and multipath, transmission without distortion channel with multiple static route, characterization of equalizers, eye diagram, types of equalizers, linear equalizer, equalizer fed back decision (DFE), automation in equalization, refresh rates Of the filter, equalizer gain update methods, blind equalization: blind equalization characteristics for the ATSC standard, GPES-godard algorithm; Adaptive equalizer length allocation: time-varying channel modeling, linear equalizer length and main jack allocation, adaptive LE equalizer, simulation parameters, simulation result, automatic DFE equalizer length allocation: adaptive DFE equalizer, parameters Of the simulation, result of the simulation; Adaptive equalizer length allocation for sparsely dispersed channels: channel modeling with sparse dispersion time variant, channel estimation, automatic allocation of DFE equalizer length for sparsely dispersed channels: pre-echo and post-echo variation of Main package, sparse packet variation, adaptive DFE equalizer for sparsely dispersed channels, parameter and result.